One-pot scalable fabrication of an oligomeric phosphoramide towards high-performance flame retardant polylactic acid with a submicron-grained structure. (15th February 2020) - Xue, Yijiao; Shen, Mingxia; Zheng, Yifei; Tao, Wenzhu; Han, Yanxin; Li, Weidong; Song, Pingan; Wang, Hao
Abstract: Last years have witnessed great advances in minimizing the flammability of the polylactic acid (PLA) bioplastic. Unfortunately, to date there remains an urgent lack of a facile strategy to develop highly effective flame retardants for PLA. Herein, we report one-pot scalable fabrication of an oligomeric phosphoramide, phenyl phosphonic piperazine (PPP), via a one-step condensation polymerization. PPP can finely disperse within the PLA matrix showing a submicron-grained structure with a domain size of 100–300 nm. The addition of 3 wt% PPP increases the limiting oxygen index (LOI) of PLA to 32.5 vol%, and a V-0 rating is achieved. Such high flame retardancy is mainly attributed to the free radical quenching, gas dilution and the thermal barrier action of the char layer. Moreover, the PLA/3%PPP composite retains a tensile strength of 55.4 MPa. This work provides a facile and scalable approach to preparing high-performance flame retardant PLA materials. Graphical abstract: Image 1 Highlights: An oligomeric polyphosphoramide (PPP) was facilely synthesized by a one-pot condensation reaction. The PLA/PPP composites exhibit unique submicron-grained microstructures. Adding only 3 wt% PPP enables PLA to achieve V-0 rating and an LOI value as high as 32.5%. The flame retardancy of PPP is mainly attributed to the radical quenching effect of and gas dilution effects. The final PLA maintains high mechanical strength due to uniform dispersion of PPP and strong interfaces.